Teachers' Perceptions on the Implementation of Student-Centered Learning in Indonesian Language Learning to Improve 21st Century Skills Among High School Students - Widodo, Mulyanto; Sumarta, I Wayan Ardi; Samhati, Siti (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This study aims to describe teachers' knowledge regarding the implementation of Student-Centered Learning (SCL) in Indonesian language instruction to enhance students' 21st-century skills. The research employs a descriptive qualitative-quantitative approach aimed at exploring the perspectives of high school Indonesian language teachers. The research sample consists of 16 Indonesian language teachers from various public and private high schools in Bandar Lampung City. Data were analyzed using descriptive techniques to identify patterns related to socio-demographic factors, teacher knowledge of SCL, implementation practices, and teacher views. This study found that Indonesian language teachers at senior high schools in Bandar Lampung have a good understanding of SCL, including its concept, benefits, challenges, strategies, and implementation. In general, they perceive the implementation of SCL in Indonesian language instruction as quite effective and believe that it can enhance students’ achievement and motivation in developing 21st-century skills.